2006
DOI: 10.1093/rheumatology/kel147
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the cost and health status consequences of treatment with TNF antagonists in patients with psoriatic arthritis

Abstract: With limited data currently available, the potential cost-effectiveness of etanercept in DMARD failures for adults with PsA appears encouraging. The result for other TNF antagonists will depend on how their relative efficacy and drug price compares with etanercept. A number of limitations are described and priorities for further research suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 27 publications
3
50
0
2
Order By: Relevance
“…Previously costeffectiveness models of biologicals assumed linear relationship between functional status (HAQ) and direct costs in PsA based on RA data [12][13]. Huscher et al [4] confirmed this relation of total costs based on a PsA study and our results pointed out the same with HAQ.…”
Section: Discussionsupporting
confidence: 82%
“…Previously costeffectiveness models of biologicals assumed linear relationship between functional status (HAQ) and direct costs in PsA based on RA data [12][13]. Huscher et al [4] confirmed this relation of total costs based on a PsA study and our results pointed out the same with HAQ.…”
Section: Discussionsupporting
confidence: 82%
“…Direct health-care resources were collected prospectively for all patients for hospitalisations, surgical interventions and RA medications. Based on this study, Bansback et al 130 separately applied a linear regression model to estimate the relationship between HAQ-DI score and resource use (Equation 2). The regression estimates were subsequently reduced by 15% to account for expenditure on DMARDs and to avoid double counting other drug acquisition costs which were separately estimated.…”
Section: Summary Of Resource Utilisation and Costs Data Used In The Ymentioning
confidence: 99%
“…The update of the results with data records of longitudinal databases will be needed to verify these findings. The analysis of TNF antagonists in Psoriatic Arthritis found that the ETN in patients who have previously failed other treatments DMARD was encouraging; but limitations in available data make it difficult to draw definitive conclusions (44). The results on short-term cost-effectiveness of ETN compared with cyclosporine or LEF are not worthwhile.…”
Section: Economic Evaluations Of the Rheumatic Diseasesmentioning
confidence: 99%